KONFLIK DALAM BINGKAI SOSIAL KEAGAMAAN - Didik Kusno Aji (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
This article tries to explain associated with various conflicts resulting from a false understanding of the text in response to a context. Text sometimes translated in a way that is narrow and indiscriminate, resulting in a narrow understanding of people and tend to be wrong.Apart from a narrow understanding conveyed by religious leaders, the real conflict in society is due to the knowledge of understanding of individuals who tend to be limited. In the global society, the paradigm of a narrow understanding that should be fought, because in turn, peacefulness will never arise when religious believers insists assume that the religion which he believes most true and other religions shall be fought and led to other religions. Then there must be understanding in the community comprehensive of religious attitudes in order to create a more harmonious atmosphere